Staphylococcus saccharolyticus Isolated From Blood Cultures and Prosthetic Joint Infections Exhibits Excessive Genome Decay - Brüggemann, Holger; Poehlein, Anja; Brzuszkiewicz, Elzbieta; Scavenius, Carsten; Enghild, Jan J.; Al-Zeer, Munir A.; Brinkmann, Volker; Jensen, Anders; Söderquist, Bo (Frontiers in Microbiology, 2019)
The slow-growing, anaerobic, coagulase-negative species Staphylococcus saccharolyticus is found on human skin and in clinical specimens but its pathogenic potential is unclear. Here, we investigated clinical isolates and sequenced the genomes of seven strains of S. saccharolyticus. Phylogenomic analyses showed that the closest relative of S. saccharolyticus is Staphylococcus capitis with an average nucleotide identity of 80%. Previously sequenced strains assigned to S. saccharolyticus are misclassified and belong to S. capitis. Based on single nucleotide polymorphisms of the core genome, the population of S. saccharolyticus can be divided into two clades that also differ in a few larger genomic islands as part of the flexible genome. An unexpected feature of S. saccharolyticus is extensive genome decay, with over 300 pseudogenes, indicating ongoing reductive evolution. Many genes of the core metabolism are not functional, rendering the species auxotrophic for several amino acids, which could explain its slow growth and need for fastidious growth conditions. Secreted proteins of S. saccharolyticus were determined; they include stress response proteins such as heat and oxidative stress-related factors, as well as immunodominant staphylococcal surface antigens and enzymes that can degrade host tissue components. The strains secrete lipases and a hyaluronic acid lyase. Hyaluronidase as well as urease activities were detected in biochemical assays, with clade-specific differences. Our study revealed that S. saccharolyticus has adapted its genome, possibly due to a recent change of habitat; moreover, the data imply that the species has tissue-invasive potential and might cause prosthetic joint infections.